2020
DOI: 10.5093/ejpalc2020a8
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards School Violence Questionnaire, Revised Version: CAHV-28

Abstract: School coexistence/violence is often the subject of social alarm. There is no consensus on the prevalence of violent behavior in the classroom, but there does seem to be about its differences according to sex, socioeconomic level, or the importance of preventive interventions for its reduction. Models consider attitudes towards violence as an indicator of risk for its expression. The objectives of this study are to explore the psychometric properties of the revised version of Cuestionario de Actitudes Hacia la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…In the present study, we used a qualitative research design for the analysis of attitudes toward violence targeting the LGBTQIA+ community at school. A large part of the published studies about the attitude–behavior relationship uses a quantitative approach [ 23 , 26 , 27 ]. Quantitative methodology, although essential for the investigation of this phenomenon, hardly captures the participants’ subjective perspective.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we used a qualitative research design for the analysis of attitudes toward violence targeting the LGBTQIA+ community at school. A large part of the published studies about the attitude–behavior relationship uses a quantitative approach [ 23 , 26 , 27 ]. Quantitative methodology, although essential for the investigation of this phenomenon, hardly captures the participants’ subjective perspective.…”
Section: Methodsmentioning
confidence: 99%
“…Sometimes, the use of tools with closed questions does not allow delving into the specificity of the attitude-behavior relationship necessary for its study and/or understanding [ 21 ]. Qualitative studies allow us to explore attitudes toward violence from the perspective of minors, with a sufficient level of specificity [ 22 , 23 ] and they are a necessary complement to quantitative studies. Nevertheless, no previous studies have been found that assume a qualitative perspective that explore the relationship between attitudes toward violence against the LGBTQIA+ community and the violence against the aforementioned in a school context.…”
Section: Introductionmentioning
confidence: 99%
“…Suicide represents a very important issue in public health. Our research departs from previous research recommendations [1], and we tried to develop an instrument to achieve a better understanding about the attitudes towards suicide.It is estimated that in 2015 there were about 788,000 deaths caused by suicide [2]. In Europe, previous research has shown that suicide rates range from 30.8 per 100,000 inhabitants to 2.2.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this ambiguity, it is difficult to evaluate how to approach suicide in the press. Since suicide is a very controversial topic, it is very difficult to assess attitudes towards it [1]. To solve this trouble, and for a better understanding of the phenomenon, we have developed an instrument following the previous recommendation for the evaluation of the perception of suicide utility in press [1].…”
Section: Introductionmentioning
confidence: 99%
“…Also, attitudes and beliefs towards violence have been also explored with the CAHV-25 and CONVIVE tools, obtaining a revised version of the tool, testing primary and secondary students in Murcia, Spain. It was also applied in multiple contexts and translated in other languages, but the original consistency found was not very high, and the used of reverse items could have led to confusion, responded bias and lacked robust indicators in factor analysis [ 68 , 71 ].…”
Section: Introductionmentioning
confidence: 99%